Comparing of retention of cast crowns cemented with two kind of permanent cement with and without prier use of temporary cement - M Sabouhi; S Nosouhian; F Naderi nabee (Isfahan University of Medical Sciences, 2008)
Introduction: This study evaluated the effects of eugenol -free temporary cement remnants on the retentive strength of casting crowns luted via zinc phosphate and resin cement (Maxcem) to the tooth structure. Material and methods: 40 extracted human molars ware randomly divided into 2 groups. each group was then divided into 2 subgroups and the teeth were paired so that the size of each tooth in each subgroup was the same as a tooth in the other subgroups. 40 standardized Ni-cr complete crowns were made on teeth prepared with a milling machine using conventional laboratory techniques. For each adhesive system, in one subgroups a provisional restoration was cemented using an eugenol -free temporary cement. Temporary crown was remained on the tooth structure for an hour and then extracted and cement remnant was removed by an excavator. Then the casing crowns were adhesively luted via zinc phosphate, adhesive resin(Maxcem) to prepared teeth. After 24h storage in distilled water, Retention was evaluated by measuring the tensile force required to dislodge the crowns from tooth preparations with a universal testing machine after thermo cycling (1500 cycles between 5c and 55c with 1- minute dwell times). The data were analyzed by means of paired T-test and wilcoxon test in SPSS software version 11.5Results: The analysis showed the mean retentive strength for 2 subgroups with and without prior use of temporary cement in the maxcem group was 176 ± 55 and 274 ± 169 N, there was not a significant difference between the 2 subgroups. (p value = 0.174). And the mean retentive strength for 2 subgroups with and without prior use of temporary cement in the zincphosphate group was 257 ± 125 and 238 ± 135 N, there was not significant difference between the 2 subgroups (p value = 0.782).Discussion: The use of an eugenol -free temporary cement does not alter the retentive strength of casting restorations lutted to prepared teeth using the tested adhesive system, when temporary cements are removed properly.Keywords: Retention, temporary cement zinc phosphate cement, Resin cement, cast restoration